2015
DOI: 10.1038/sj.bdj.2015.711
|View full text |Cite
|
Sign up to set email alerts
|

Differences by age and sex in general dental practitioners' knowledge, attitudes and behaviours in delivering prevention

Abstract: Although dentists in this study may lack some core preventive knowledge, many expressed very positive attitudes towards prevention and reported to be routinely offering a range of preventive measures. Younger and female dentists tended to engage more frequently in preventive activities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
39
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 30 publications
(43 citation statements)
references
References 22 publications
0
39
4
Order By: Relevance
“…The age association was reported by another study conducted among dentists in Hong Kong 10 , however another study conducted in the UK found that young dentists are more likely to give smoking cessation support 26 . In general, older age for dentists means more professional maturation as well as financial and professional stability.…”
Section: Discussionmentioning
confidence: 76%
“…The age association was reported by another study conducted among dentists in Hong Kong 10 , however another study conducted in the UK found that young dentists are more likely to give smoking cessation support 26 . In general, older age for dentists means more professional maturation as well as financial and professional stability.…”
Section: Discussionmentioning
confidence: 76%
“…Despite these findings, it has been suggested that health professionals hold positive beliefs regarding the importance of diet counselling (14) and that effective dietary screening and counselling play a key role in the detection of potential risk factors for nutrition-related problems in patients with chronic disease or conditions (12). These results suggest that there may be barriers present preventing the provision of dietary advice by health professionals.…”
Section: Introductionmentioning
confidence: 99%
“…Literature reports that dentists' attitudes towards prevention are positive and in a study by Yusuf et al 19 there were high levels of self-reported routine provision of preventive care. Yet, the same study also revealed low levels of knowledge on basic preventive messages, in particular on the recommendations on fluoride concentration for toothpastes and the recommended frequency of topical fluoride varnish application.…”
Section: Discussionmentioning
confidence: 96%